Examining the Legal Responsibilities and Key Challenges of Personal Representatives in Malaysian Inheritance Management - Drs Nasrul, Muhammad Amrullah; Zairin Zain, Anis A'fifah; Wan Mohd Salim, Wan Noraini (UI Scholars Hub, 2025)
Personal representative connotes a person authorised under the law to manage the estate of the deceased person. The personal representative is responsible to gather all the assets belonging to the deceased and distribute the assets to the beneficiaries legally. The process of inheritance management in Malaysia requires a formal application to be made to the administrative bodies for the appointment of a personal representative, either as an executor or administrator. However, instances of misappropriation of the deceased’s estate by personal representatives have raised serious concerns, affecting the proper administration of estates and the rights of beneficiaries This study emphasises on the highlighted issue based on their frequency of recurrence, which calls for prompt attention and resolution from the socio-legal perspective. The research method adopted under this study involves library-based research, which focuses on a review of legal texts, case law, academic journals, and statutory provisions including but not limited to the Distribution Act 1958, Federal Constitution and Small Estate (Distribution) Act 1955. The study found that having comprehensive knowledge of the rights and duties of personal representatives is paramount in ensuring the completion of inheritance management. This is coupled with the elements of trust and honesty expected to be exercised by the personal representative to ensure smoothness and consistency in inheritance management.